Clinical Outcomes Associated with Thermal Pulsation System Treatment. Issue 9 (September 2015) - Satjawatcharaphong, Pam; Ge, Shaokui; Lin, Meng C.
ABSTRACT Purpose To identify patient characteristics at a baseline ocular surface evaluation that correlate with improvement in dry eye symptoms at a follow-up visit after treatment with the LipiFlow Thermal Pulsation System. Methods Thirty-two patients completed a comprehensive baseline ocular surface evaluation and were treated with the LipiFlow Thermal Pulsation System followed by maintenance home therapy. Lipid layer thickness and blink pattern were determined using the LipiView Interferometer. Noninvasive tear breakup time was measured using a Medmont E300 Corneal Topographer. Slit lamp biomicroscopy was used to evaluate invasive tear breakup time and corneal staining after instillation of fluorescein dye. Conjunctival staining, location of the line of Marx, and presence of lid wiper epitheliopathy were evaluated with lissamine green dye. Meibomian gland expressibility was scored using the TearScience Meibomian Gland Evaluator, and meibography was imaged using the Oculus Keratograph. A logistic regression model was used to estimate the odds ratios for having a decreased posttreatment score (reduced symptoms) of Standard Patient Evaluation of Eye Dryness (SPEED). Results Baseline SPEED score (p = 0.01) and sex (p = 0.03) had significant odds ratios at the α = 0.05 level. Baseline noninvasive tear breakup time (p = 0.07), number of grade 0 meibomian glands in the lower lid (p = 0.09), and conjunctival staining grade in the inferior region (p = 0.10) met an α = 0.10 criterion for significant odds ratios, but not the typical α = 0.05 criterion. Higher baseline SPEED score and male sex had greater odds for decreased posttreatment SPEED score. Conclusions Our results identified factors that better select candidates for LipiFlow Thermal Pulsation System.